1996
DOI: 10.1103/physrevb.53.2101
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of atomic-scale sliding friction

Abstract: Simulation studies of atomic-scale sliding friction have been performed for a number of tip-surface and surface-surface contacts consisting of copper atoms. Both geometrically very simple tip-surface structures and more realistic interface necks formed by simulated annealing have been studied. Kinetic friction is observed to be caused by atomic-scale stick and slip which occurs by nucleation and subsequent motion of dislocations preferably between close-packed ͕111͖ planes. Stick and slip seems to occur in dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
200
3
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(218 citation statements)
references
References 32 publications
(58 reference statements)
11
200
3
1
Order By: Relevance
“…Zhong et al (2003) also reported that the wear decreased significantly when the sliding surfaces where parallel to the (111) planes compared to the (100) planes. Further, Sorensen et al (1996) have shown that between a Cu tip and Cu surface, with non-matching surfaces parallel to the (111) plane the wear is minimum. Although, the most favorable case of (111) parallel to the sliding direction is not considered in this work, the results are comparable.…”
Section: Effect Of Lattice Orientation Hmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhong et al (2003) also reported that the wear decreased significantly when the sliding surfaces where parallel to the (111) planes compared to the (100) planes. Further, Sorensen et al (1996) have shown that between a Cu tip and Cu surface, with non-matching surfaces parallel to the (111) plane the wear is minimum. Although, the most favorable case of (111) parallel to the sliding direction is not considered in this work, the results are comparable.…”
Section: Effect Of Lattice Orientation Hmentioning
confidence: 99%
“…Song and Srolovitz (2007) performed MD simulations of single asperity contact and deformation on a flat surface over single-and multi-cycle loading and unloading. In an extensive study, Sorensen et al (1996) conducted MD simulations on atomic-scale friction of sliding copper surfaces. The dependence of the normal load, contact area, sliding velocity, temperature, and lattice mismatch was investigated with an emphasis on observing slip-stick for different tip-surface and surfacesurface contacts.…”
Section: Introductionmentioning
confidence: 99%
“…Carpick & Salmeron 1997;Gnecco et al 2007) including diamond (Germann et al 1993). Insight into the atomic-scale stick-slip phenomenon has been provided by MD simulations of two contacting diamond surfaces (Harrison et al 1992a, of a tip and a Si surface (Landman et al 1989), metal surfaces (Sorensen et al 1996) and two infinite surfaces of organic monolayers in sliding contact (Glosli & McClelland 1993;Mikulski & Harrison 2001a,b;Chandross et al 2004;Harrison et al 2004;Mikulski et al 2005a,b).…”
Section: Friction Of Crystalline Surfaces (A ) Friction Of Diamondmentioning
confidence: 99%
“…To investigate atomic scale asperities and finite contact areas, many authors (such as [119], see figure 1) have modelled AFM-like tips-on-substrate contacts. Since the shearing velocity in classical MD simulations is very high compared to real AFM experiments, Large Scale Molecular Dynamics simulations are still under development, involving massive parallel programming [120].…”
Section: Discrete Approachesmentioning
confidence: 99%